Aggressive pituitary tumours and carcinomas, characteristics and management of 171 patients. Issue 4 (19th September 2022) - Burman, Pia; Trouillas, Jacqueline; Losa, Marco; McCormack, Ann; Petersenn, Stephan; Popovic, Vera; Theodoropoulou, Marily; Raverot, Gerald; Dekkers, Olaf M; Guenego, Agathe; Micko, Alexander; Hubalewska-Dydejezky, Alicia; et al.
Abstract: Objective: To describe clinical and pathological characteristics and treatment outcomes in a large cohort of aggressive pituitary tumours (APT)/pituitary carcinomas (PC). Design: Electronic survey August 2020–May 2021. Results: 96% of 171 (121 APT, 50 PC), initially presented as macro/giant tumours, 6 were microadenomas (5 corticotroph). Ninety-seven tumours, initially considered clinically benign, demonstrated aggressive behaviour after 5.5 years (IQR: 2.8–12). Of the patients, 63% were men. Adrenocorticotrophic hormone (ACTH)-secreting tumours constituted 30% of the APT/PC, and the gonadotroph subtypes were under-represented. Five out of 13 silent corticotroph tumours and 2/6 silent somatotroph tumours became secreting. Metastases were observed after median 6.3 years (IQR 3.7–12.1) from diagnosis. At the first surgery, the Ki67 index was ≥3% in 74/93 (80%) and ≥10% in 38/93 (41%) tumours. An absolute increase of Ki67 ≥ 10% after median of 6 years from the first surgery occurred in 18/49 examined tumours. Tumours with an aggressive course from outset had higher Ki67, mitotic counts, and p53. Temozolomide treatment in 156/171 patients resulted in complete response in 9.6%, partial response in 30.1%, stable disease in 28.1%, and progressive disease in 32.2% of the patients. Treatment with bevacizumab, immune checkpoint inhibitors, and peptide receptor radionuclide therapy resulted in partial regression in 1/10, 1/6, and 3/11, respectively. Median survival in APT and PC was 17.2 and 11.3 years, respectively. Tumours with Ki67 ≥ 10% and ACTH-secretion were associated with worse prognosis. Conclusion: APT/PCs exhibit a wide and challenging spectrum of behaviour. Temozolomide is the first-line chemotherapy, and other oncological therapies are emerging. Treatment response continues to be difficult to predict with currently studied biomarkers.